From complexity responses to enacted practice: mindfulness as a multi-level metacognitive capability in project leadership - Tobias-Mortlock, Jutta; Turner, Neil; Plagnol, Anke C.; Beaumont, Anya; Bourne, Mike (Elsevier, 2026)
Project complexity research has established that structural, socio-political, and emergent complexities require different response capabilities, yet little is known about how project leaders enact these responses in practice. Drawing on practice theory and strategy-as-practice, this study examines how project leaders mobilise mindfulness as a multi-level metacognitive practice to address project complexity. We analyse qualitative data from a flagship UK government Project Leadership Programme, including open-ended survey responses (n = 58) and semi-structured interviews (n = 10) with senior project leaders. Our findings show that mindfulness is enacted at individual, team, and organisational levels to operationalise planning and control, relationship-building, and flexibility responses. Mindfulness functions both as relief, enabling leaders to regulate stress and reactivity, and as engagement, supporting sustained attention, psychologically safe dialogue, and adaptive sensemaking. We contribute to theory by extending project complexity research from identifying effective responses to explaining how response capabilities are enacted across organisational levels through socially embedded metacognitive practice. We contribute to practice by offering a scalable and context-sensitive repertoire of mindfulness practices that project leaders can embed in leadership development, governance routines, and team interactions to build sustained capability for navigating structural, socio-political, and emergent project complexity.
Keywords: Building & Construction; 33 Built environment and design; 35 Commerce, management, tourism and services; Mindfulness; Project leadership; Project management; Project complexity; Public-sector projects; Practice theory; Metacognition; Metacognitive practice